Microwave radiothermometry of knee joints in girls in pre- and pubertal periods - A. V. Tarakanov; A. A. Lebedenko; E. S. Ladanova; T. D. Tarakanova; E. G. Skorodumova; A. N. Yatsuk (Медицинский вестник Юга России, 2023)
Objective: to study the deep and skin temperatures of the knee joint by microwave radiothermometry (RTM) in healthy girls of comparable age in the pre- and pubertal periods. Materials and methods: the study was carried out in the "Problem Scientific Laboratory of Physical Methods of Diagnosis and Treatment" of Rostov State Medical University and the children's health camp "Mir" (Krasny Desant village, Rostov region). It was 45 girls aged 12 years, taking into account gender development, divided into two groups: 1st gr. (n=28)  — prepubertal period; 2nd gr. (n =17) — puberty. RTM of the knee joints was performed according to a certain scheme using the MWR2020 system (ex RTM-01-RES) (Moscow, Great Britain). Results: in the groups, the color fields of deep and skin temperature, when compared, are characterized by a slight geometric and color transformation are similar to each other; the lowest temperature is noted in the projection of the patella. Temperature fields of thermoasymmetry make it possible to reveal temperature differences in groups of subjects. In the 2-nd group, there are also higher growth and weight indicators, lower deep and skin temperature in almost all areas of the knee joint, fluctuations reach 0.4 –1.4 ° C. Conclusion: a decrease in temperature in the knee joints in pubertal girls with a relatively mature menstrual cycle reflects general changes in hormonal regulation in this period of development. When forming the temperature indicators of healthy girls, it is necessary to take into account the hormonal processes of puberty with division into groups of pre- and pubertal periods of development.